Effect of population dynamics on Livelihood Security in rural Sri Lanka (Bangladesh Journal of Public Administration, 2021)
Out of 20.82 million total population of Sri Lanka, 81.70% of the population lives in rural areas (Quandl, 2015). From 2005 to 2016 government expenditure for agriculture based actions shows the trend of decreasing while the development policy gradually changes the path from agricultural based economy to an industrial based economy over last few decades. However, poverty head count measures in 2006/2007 of Sri Lanka indicate that the percentage of people living in poverty in the rural sector is significant and the percentage of underweight children in rural areas is 38.3%, which is considerably higher than that of urban areas (29.9%). Thus, this status brought about the primary research question of how does the country achieve livelihood security. Thus, the objectives of this research are, to examine the factors affecting livelihood security and to understand the view of rural communities’ population dynamics on livelihood security. The research was carried out in mixed research design. The results show that access to livelihood resources also was not affected by gender, age, education and household income. However, in the analysis, both males and females were dissatisfied with the access to livelihood resources. Thus, in forming and implementation of development policies Sri Lanka needs to ensure community livelihood security.